The Effect of Different Hormonal Supplementations on Pregnancy Support and Outcome in Mice - Fakhrildin, Muhammad; Fadhil, Ayad; Ibrahim, M.; R., Jafar; Al-Temimie, B.; Al-Ibrahimi , H.; Asa’ad, J. (Iraqi Journal of Science, 2025)
The effectiveness of different hormonal supplementations and durations of injection on early embryonic implantation and pregnancy outcome in mice were investigated. One hundred and ainety six mothered mice were divided into two major groups depending on hormonal stimulation of estrous cycle of females either stimulated or non-stimulated. Further, cach of major group was subdivided into two minor groups depending on period of injection during gestation either for 1 week or 1" and 2nd weeks. Each minor group was divided according to type of hormone supplement Including human chorionic gonadotrophin (3 IU), progesterone (0.07 mg), estradiol (0.035 mg) or other combinations between progesterone and human chorionic gonadotrophin or estradiol. The main parameters were studied are gestation period, litter size and endometrium thickness of uterine horn. The results of the present study observed that the administration of hormones have insignificant differences in the period of gestation as compared to its control groups. Also, litter size and endometrium thickness of uterine horn were significantly (P< 0.05) increased as a result of hormonal treatments when compared to its control groups. However, progesterone supplementation for 1 and 2 weeks of gestation period was best and significantly (P<0.01) increased litter size and endometrium thickness of uterine horn without noticeable side effects. It was concluded that the synchronization of ovarian stimulation and hormonal supplementation by using either progesterone alone or in combination with human chorionic gonadotrophin may be have good results to improve normal embryonic implantation rate and enhance pregnancy nutcome. Further hormonal and histological studies are recommended to investigate the effects of different hormonal supplementations on endocrine and reproductive organs of pregnant temale.